The organized mind thinking straight in the age of information overload - Levitin, Daniel J. (Dutton, 2014)
Daniel J. Levitin, Ph.D., uses the latest brain science to demonstrate how people with "organized" minds excel--and how readers can use their methods to regain a sense of mastery over the way they organize their homes, workplaces,and lives